D* from diffusion MRI reveals a correspondence between ventricular cerebrospinal fluid volume and flow in the ischemic rodent model. Issue 4 (April 2022) - Jang, MinJung; Han, SoHyun; Cho, HyungJoon
Quantitative measurement of cerebrospinal fluid (CSF) flow and volume and longitudinal monitoring of CSF dynamics provide insights into the compensatory characteristics of post-stroke CSF. In this study, we compared the MRI pseudo-diffusion index ( D* ) of live and sacrificed rat brains to confirm the effect of ventricular CSF flow on diffusion signals. We observed the relationship between the CSF peak velocities and D* through Monte Carlo (MC) simulations to further understand the source of D* contrast. We also determined the dominant CSF flow using D* in three directions. Finally, we investigated the dynamic evolutions of ventricular CSF flow and volume in a stroke rat model ( n  = 8) from preoperative to up to 45 days after surgery and determined the correlation between ventricular CSF volume and flow. MC simulations showed a strong positive correlation between the CSF peak velocity and D* ( r  = 0.99). The dominant CSF flow variations in the 3D ventricle could be measured using the maximum D* map. A longitudinal positive correlation between ventricular CSF volume and D* was observed in the lateral ( r  = 0.74) and ventral-third ( r  = 0.81) ventricles, respectively. The directional D* measurements provide quantitative CSF volume and flow information, which would provide useful insights into ischemic stroke with diffusion MRI.